The digital disruption: unraveling the impact of digital sharia banking transformation on organizational culture and employee engagement - Johan Budiman; Edy Junaedi; Hafiz Abdillah; M.A Naufal Algifariy (Proceeding of National Conference on Accounting & Finance, 2026)
The Indonesian Sharia banking sector stands at a critical juncture, mandated by regulators to significantly increase its market share amidst intense competition from conventional and Islamic FinTech. While digital transformation (DT) is hailed as the pathway to growth, its high failure rate is often attributed to neglected human factors. This study investigates the human element of DT within the unique, values-based context of Sharia banking. A cross-sectional quantitative study was conducted, collecting data via a structured online questionnaire from 293 employees of a major Indonesian Sharia bank undergoing corporate-wide digital transformation. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3. The findings provide robust, empirical evidence that the positive impact of digital transformation on employee engagement is not direct but is fully mediated by the development of a digital-ready organizational culture. This study makes a distinct contribution by demonstrating that in Sharia banks where culture is intrinsically linked to Sharia principles like maslaha (public interest) and ta'awun (cooperation) strategic investment in cultivating a supportive, adaptive culture is not merely beneficial but is a prerequisite for unlocking employee engagement and achieving successful digital modernization.